POLA PIKIR KELAS ELITE DALAM PERUMUSAN PERUNDANG-UNDANGAN DI INDONESIA - Sarip Sarip (Jurnal De Jure Muhammadiyah Cirebon, 2017)
The mindset of the elite class in the formulation of legislation. In the context of the formation of the Act, freedom of expression is a condition for listening to popular opinions. Listening aims to know the opinions of all the people, not a few people. Such knowledge will be the basis of legislative consideration in approving a bill. However, the mindset of the elite class is sometimes confusing even still see the formation of legislation should impose its will. At the level of application the community becomes a victim due to the mindset of an elite class that is not yet mature enough in thinking related to its task. Keywords: the formulation of legislation, legislative and elite class.